A Class of Integral Operators Preserving Subordination and Superordination. (3rd February 2008) - Cho, Nak Eun; Kim, In Hwa
Abstract : We give some subordination- and superordination-preserving properties of certain nonlinear integral operators defined on the space of normalized analytic functions in the open unit disk. The sandwich-type theorems for these integral operators are also obtained. Moreover, we consider an application of the subordination and superordination theorems to the Gauss hypergeometric function.